2020
DOI: 10.5114/ceji.2020.94710
|View full text |Cite
|
Sign up to set email alerts
|

Circulation autoantibodies against C-terminus of NuMA in patients with Behçet’s disease

Abstract: Circulating autoantibodies have a close association with autoimmune diseases, which may be seen even in healthy individuals. These are also considered as promising source of new biomarkers in various autoimmune diseases. however, their profile is not completely understood till now. here, we evaluated autoantibodies against nuclear mitotic apparatus protein located at the carboxy terminus (C-nuMa) in blood circulation of han Chinese patients, using different technical approaches to discover pathological reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Autoantibodies were observed in patients with BD and reacted with an endothelial cell antigen, α-enolase (a positive rate of 38% by an ELISA) ( 85 ), a ubiquitously expressed membrane protein, prohibitin (28% by an ELISA) ( 86 ), α-tropomyosin (22% by an ELISA) ( 87 ), the nuclear mitotic apparatus protein (NuMA; 28% by an ELISA) ( 88 ), a riboflavin-containing flavoprotein (41% by an ELISA) ( 89 ), a membrane protein annexin A2 (34% by an ELISA) ( 90 ), a microtubule-related protein, kinectin (23% by an immunoprecipitation assay) ( 91 ), and an actin-binding protein, cofilin-1 (13% by western blotting; Figure 2A ) ( 92 ). Thus, BD demonstrates a mixed pattern of autoinflammatory and autoimmune diseases within the spectrum ( 14 ).…”
Section: Behçet Diseasementioning
confidence: 99%
“…Autoantibodies were observed in patients with BD and reacted with an endothelial cell antigen, α-enolase (a positive rate of 38% by an ELISA) ( 85 ), a ubiquitously expressed membrane protein, prohibitin (28% by an ELISA) ( 86 ), α-tropomyosin (22% by an ELISA) ( 87 ), the nuclear mitotic apparatus protein (NuMA; 28% by an ELISA) ( 88 ), a riboflavin-containing flavoprotein (41% by an ELISA) ( 89 ), a membrane protein annexin A2 (34% by an ELISA) ( 90 ), a microtubule-related protein, kinectin (23% by an immunoprecipitation assay) ( 91 ), and an actin-binding protein, cofilin-1 (13% by western blotting; Figure 2A ) ( 92 ). Thus, BD demonstrates a mixed pattern of autoinflammatory and autoimmune diseases within the spectrum ( 14 ).…”
Section: Behçet Diseasementioning
confidence: 99%
“…The tissue sections of the ulcers isolated from BD patients revealed that serum IgA autoantibodies colocalized with monoclonal antibodies against hnRNP A2/B1 (Cho, Zheng, Cho, et al, 2013). In addition, hnRNP C1/C2 and hnRNP A1 were also identified as potential autoantigens in BD and the positivity of hnRNP A1 autoantibodies was associated with the deep vein thrombosis (Chen et al, 2016; Hussain et al, 2018).…”
Section: Hnrnps Are Autoantigens In Autoimmune Diseases and Associate...mentioning
confidence: 99%